Nonlinear model predictive control applied to spacecraft attitude control (Closed-loop stability and optimality with thrusters and wheels) - Atsushi SAKAMOTO; Yuichi IKEDA; Isao YAMAGUCHI; Takashi KIDA (Nihon Kikai Gakkai ronbunshu, 2016)
This paper studies model predictive control (MPC) for spacecraft nonlinear attitude control with actuator input nonlinearities. This technology is important to achieve high-rate large angle attitude maneuver problems of recent spacecraft missions. To this end, we first derive linear matrix inequality (LMI) conditions to ensure input-to-state stability (ISS) or asymptotic stability (AS) of MPC closed-loop systems for standard actuators such as reaction control systems (RCS) and reaction wheels (RW). After providing optimization algorithms based on branch and bound methods, we evaluate and compare the control performance of each case using RW, RCS and both RCS and RW in combination through numerical simulations for astronomical observation satellite.